Acteoside ameliorates cerebral ischemia/reperfusion injury in MCAO rats as a natural plasma Kallikrein inhibitor from Osmanthus fragrans flower - Hui-hao Wang; Kai-rui Feng; Ping Li; Zhi-Yong Wang; Li Liu (Scientific Reports)
Abstract Acteoside is the potential bioactive component of Osmanthus fragrans flowers for treating stroke. However, the pharmacological actions, therapeutic targets and underlying mechanisms of acteoside in cerebral ischemia/reperfusion injury remain poorly understood. In this study, we investigated the therapeutic effect, direct target, and the underlying mechanisms of acteoside on cerebral I/R injury in middle cerebral artery occlusion (MCAO) rats. Our study suggested that treatment with OFFE or acteoside significantly reduced cerebral infarct area in MCAO rats. Coagulation function measurement suggested that acteoside treatment increased activated partial thromboplastin time (APTT) and prothrombin time (PT) in vitro. Further molecular docking and enzyme activity assays indicated that acteoside binds to plasma kallikrein (pKal) and markedly inhibits its activity. RNA sequencing, ELISA, and Western blotting revealed that acteoside regulated coagulation to mitigate inflammation by modulating NF-κB signaling and inhibite oxidative stress by suppressing NOX2/NOX4 pathways. These findings reveal that acteoside exerts protective effects against cerebral I/R injury in MCAO rats by attenuating inflammation and oxidative stress as a natural plasma kallikrein inhibitor.